2010
DOI: 10.1080/00051144.2010.11828351
|View full text |Cite
|
Sign up to set email alerts
|

Applying Optimal Sliding Mode Based Load-Frequency Control in Power Systems with Controllable Hydro Power Plants

Abstract: In this paper an optimal load-frequency controller for a nonlinear power system is proposed. The mathematical model of the power system consists of one area with several power plants, a few concentrated loads and a transmission network, along with simplified models of the neighbouring areas. Firstly, a substitute linear model is derived, with its parameters being identified from the responses of the nonlinear model. That model is used for load-frequency control (LFC) algorithm synthesis, which is based on disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As the general analytical solution has not been found [20], it was concluded that stability can be guaranteed if the control signal sampling time is different from the sampling time of the measured output samples. Such a control concept is called multirate output feedback [21][22][23]. The fast output sampling (FOS) method is based on sampling the output signal with higher frequency than the frequency of the control signal samples.…”
Section: Fast Output Sampling Algorithmmentioning
confidence: 99%
“…As the general analytical solution has not been found [20], it was concluded that stability can be guaranteed if the control signal sampling time is different from the sampling time of the measured output samples. Such a control concept is called multirate output feedback [21][22][23]. The fast output sampling (FOS) method is based on sampling the output signal with higher frequency than the frequency of the control signal samples.…”
Section: Fast Output Sampling Algorithmmentioning
confidence: 99%
“…Sliding‐mode control has many attractive features such as insensitivity to the model errors and parametric uncertainties . Given its advantages, SMC provides powerful techniques to complicated nonlinear dynamic systems for tracking control, including robotic manipulator systems, active suspension vehicle systems, induction motor drive systems, power systems, and spacecraft systems …”
Section: Introductionmentioning
confidence: 99%
“…In [20,21], two kinds of sliding-mode governors were investigated for hydropower plants. Other reports can be found in [22][23][24]. Usually, one assumption in most of the referred articles is that all the state variables of hydro power systems are measurable.…”
Section: Introductionmentioning
confidence: 99%